Technological and Institutional Innovations for Marginalized Smallholders in Agricultural Development - Gatzweiler, Franz W.; von Braun, Joachim (Springer International Publishing : Imprint: Springer, 2016)
The aim of the book is to present contributions in theory, policy and practice to the science and policy of sustainable intensification by means of technological and institutional innovations in agriculture. The research insights re from Sub-Saharan Africa and South Asia. The purpose of this book is to be a reference for students, scholars and practitioners inthe field of science and policy for understanding and identifying agricultural productivity growth potentials in marginalized areas.